2013
DOI: 10.3758/s13428-013-0336-z
|View full text |Cite
|
Sign up to set email alerts
|

Using Arduino microcontroller boards to measure response latencies

Abstract: Latencies of buttonpresses are a staple of cognitive science paradigms. Often keyboards are employed to collect buttonpresses, but their imprecision and variability decreases test power and increases the risk of false positives. Response boxes and data acquisition cards are precise, but expensive and inflexible, alternatives. We propose using open-source Arduino microcontroller boards as an inexpensive and flexible alternative. These boards connect to standard experimental software using a USB connection and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 11 publications
0
40
0
Order By: Relevance
“…Another benefit of the Arduino microcontroller more generally is that it is expandable and can be programmed to communicate with a large range of devices that read serial protocol. A user is not limited to using an FSR as used in the present study but may, instead, use a piezo element to record tap vibrations, a circular potentiometer for circle drawing, or a simple button similar to a computer keyboard key (see Schubert et al, 2013). The drum pads used in videogames, such as Rock Band, and the percussion pad tested here use the piezo elements to record onsets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another benefit of the Arduino microcontroller more generally is that it is expandable and can be programmed to communicate with a large range of devices that read serial protocol. A user is not limited to using an FSR as used in the present study but may, instead, use a piezo element to record tap vibrations, a circular potentiometer for circle drawing, or a simple button similar to a computer keyboard key (see Schubert et al, 2013). The drum pads used in videogames, such as Rock Band, and the percussion pad tested here use the piezo elements to record onsets.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (e.g., D 'Ausilio, 2012;Schubert, D'Ausilio, & Canto, 2013) have shown that the Arduino can record response latencies with less than 1-ms variability. The Arduino uses an internal clock that can record response times with microsecond precision.…”
Section: Abstract Auditory Feedback Sensorimotor Synchronization mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Besson et al [10] these boards are able to record different types of events associated with electrical [11], optical [12] or mechanical signals [13,14].…”
Section: Using Microcontroller Arduino As the Control Elementmentioning
confidence: 99%
“…As a matter of fact, the idea was to use a combination of a ZigBee radio transceiver provided by Microchip [9] and an "Arduino" microcontroller [10]. Our designed node showed satisfying results in terms of energy saving and the reliability of data processing.…”
Section: Introductionmentioning
confidence: 99%